TAAR1 Expression in Human Macrophages and Brain Tissue: A Potential Novel Facet of MS Neuroinflammation - David A. Barnes (MDPI AG, 2021)
TAAR1 is a neuroregulator with emerging evidence suggesting a role in immunomodulation. Multiple sclerosis (MS) is an immune-mediated demyelinating disease of the central nervous system. Here, we investigate TAAR1 expression in human primary monocytes, peripherally-derived macrophages, and MS brain tissue. RT-qPCR was used to assess TAAR1 levels in MS monocytes. Using a previously validated anti-human TAAR1 antibody and fluorescence microscopy, TAAR1 protein was visualized in lipopolysaccharide-stimulated or basal human macrophages, as well as macrophage/microglia populations surrounding, bordering, and within a mixed active/inactive MS lesion. In vivo, TAAR1 mRNA expression was significantly lower in MS monocytes compared to age- and sex-matched healthy controls. In vitro, TAAR1 protein showed a predominant nuclear localization in quiescent/control macrophages with a shift to a diffuse intracellular distribution following lipopolysaccharide-induced activation. In brain tissue, TAAR1 protein was predominantly expressed in macrophages/microglia within the border region of mixed active/inactive MS lesions. Considering that TAAR1-mediated anti-inflammatory effects have been previously reported, decreased mRNA in MS patients suggests possible pathophysiologic relevance. A shift in TAAR1 localization following pro-inflammatory activation suggests its function is altered in pro-inflammatory states, while TAAR1-expressing macrophages/microglia bordering an MS lesion supports TAAR1 as a novel pharmacological target in cells directly implicated in MS neuroinflammation.